A look at the procedural guarantees and rights granted to IDP populations by the Constitutional Court of Colombia and their enforcement within the 1448 Act of 2011 in the section of land restitution - Vega-Pérez, Leonel; Gutiérrez-Sánchez, Robinson D.; Riaño M., Liliana Andrea; Barrera C., Siomara Lucía; Alvarado O., María Claudia; Ortega D., Mayerli Jhoana; Díaz, Diana Marcela; Acuña-R., Fabiola Esperanza; Rodriguez, Diego Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2014)
In Colombia has been triggered an internal armed conflict for land tenure, as a result of social inequalities and ideological diversity, causing a series of displacements of the civilian population and systematic violations of the rights of our farmers, especially those located in rural areas of the country. This situation has led to constant intervention of foreign governments, NGOs and IDP populations, and the issue of the 1448 Act of 2011, named «Law of Victims and Restitution of Land”, which seeks to meet the needs of the vulnerable population, in order to ensure the restoration of the rights which had the population before the dispossession of their lands. The Colombian Constitutional Court, meanwhile, in its continuing statements, has established procedural guarantees and has granted rights to IDP population, to fully comply with the laws and programs convened by the government.